Scientific contributions and lessons learned from 30 years of ecological monitoring of the Bylot Island tundra ecosystem - Gauthier, Gilles; Berteaux, Dominique; Bêty, Joël; Legagneux, Pierre; Fauteux, Dominique; Gravel, Dominique; Cadieux, Marie-Christine (Frontiers in Ecology and Evolution, 2024)
The Arctic tundra has a relatively low biodiversity but species living there have unique adaptations and are exposed to unprecedented rates of climate warming. Monitoring changes in Arctic biodiversity and identifying the driving forces is thus a pressing issue. Bylot Island in the Canadian Arctic has one of the longest and most comprehensive monitoring programs of the tundra food web, spanning four decades. We provide a historical overview of ecological studies on Bylot Island, summarize their key scientific contributions, show their impacts, and present the ingredients for the success of the program and the main challenges encountered. Some major contributions include demonstrating the key role of predation in structuring the tundra food web, the importance of exchanges between ecosystems for the persistence of top predators and their cascading effects on trophic interactions, the apparent resistance of the vertebrate biota to climate warming, the need to consider multiple hypotheses to explain northward range expansion of species and the benefits of integrating scientific data and local knowledge into ecological monitoring. The program has produced >250 journal articles and >80 graduate student theses, which generated >7,700 citations in the scientific literature. A high proportion (65%) of the articles had more citations than comparable publications in their field. The longevity and success of the program can be attributed to several factors, including a researcher-driven (i.e. bottom-up) approach to design the monitoring; long-term commitment of a small number of dedicated researchers and the strong participation of graduate students; the adoption of a food web rather than a single species perspective; extensive presence in the field; the combination of several methodological approaches; and the use of multiple spatial scales adapted to research questions of interest. Challenges encountered include funding issues, transfer of expertise over time, limited spatial replication, statistical design and maintaining partnerships. Robust monitoring is essential to provide sound baseline to detect future changes, and lessons learned from our program could improve future monitoring schemes in the Arctic. Paradoxically, we believe that ecological monitoring on Bylot Island has been successful in large part because it was not originally designed as a monitoring program per se.